Suitability of the Coralline Alga Clathromorphum compactum as an Arctic Archive for Past Sea Ice Cover. Issue 1 (30th December 2021) - Leclerc, Natasha; Halfar, Jochen; Hetzinger, Steffen; Chan, Phoebe T. W.; Adey, Walter; Tsay, Alexandra; Brossier, Eric; Kronz, Andreas
Abstract: Arctic sea ice cover has been steeply declining since the onset of satellite observations in the late 1970s. However, the available annually resolved sea ice data before this time are limited. Here, we evaluated the suitability of annual trace element (Mg/Ca) ratios and growth increments from the long‐lived annual increment‐forming benthic coralline red alga, Clathromorphum compactum, as high‐resolution sea ice cover archive. It has previously been shown that the growth of C. compactum is strongly light controlled and therefore greatly limited during the polar night and underneath sea ice cover. We compare algal data from 11 sites collected throughout the Canadian Arctic, Greenland, and Svalbard, with satellite sea ice data. Our results suggested that algal growth anomalies most often produced better correlations to sea ice concentration than Mg/Ca ratios or when averaging growth and Mg/Ca anomalies. High Arctic regions with persistently higher sea ice concentrations and shorter ice‐free seasons showed the strongest correlations between algal growth anomalies and satellite sea ice concentration over the study period (1979–2015). At sites where ice breakup took place before the return of sufficient solar irradiance, algal growth was most strongly tied to a combination of solar irradiance and other factors such as temperature, suspended sediments, phytoplankton blooms, and cloud cover. These data are the only annually resolved in situ marine proxy data known to date and are of utmost importance to gain a better understanding of the sea ice system and to project future sea ice conditions. Plain Language Summary: Natural layered structures such as tree rings and mollusk shells' growth layers archive environmental data in their rings or layers as they grow. A lesser known and emerging environmental archive is the coralline red algae species, Clathromorphum compactum, that lives on the Arctic and North Atlantic seafloor (10–30 m deep). It grows on solid substrate by forming a new calcified layer of growth every year, ultimately building up dome‐like crusts over tens or hundreds of years. Different thicknesses of their annual layers depend on ocean temperature and sunlight availability. Because sea ice forms under cold conditions and blocks sunlight from reaching the sea floor, we hypothesized that growth also responds to sea ice conditions. Here, we evaluated the relationship between algal layer thicknesses and/or magnesium chemistry to sea ice data derived from satellite images at 11 sites. Strong relationships between algal growth and sea ice cover were found at exposed sites with longer seasonal‐ice cover duration. Recent reductions of sea ice in certain regions have weakened the growth‐sea ice relationship. A deeper understanding of past ice conditions can provide extremely valuable data for climate models to more accurately predict future sea ice scenarios. Key Points: Annual proxy anomalies from growth increments and Mg/Ca ratios in calcareous algae were compared to satellite sea ice concentrations Algal growth anomalies most significantly correlated to sea ice concentrations at sites with medium wave exposure and >5 months sea cover Downsampled to 5‐year averages, correlations are strengthened and can capture summer sea ice variability better than annual averages